2016
DOI: 10.1152/jn.00096.2016
|View full text |Cite
|
Sign up to set email alerts
|

Reduced frontal theta oscillations indicate altered crossmodal prediction error processing in schizophrenia

Abstract: Our brain generates predictions about forthcoming stimuli and compares predicted with incoming input. Failures in predicting events might contribute to hallucinations and delusions in schizophrenia (SZ). When a stimulus violates prediction, neural activity that reflects prediction error (PE) processing is found. While PE processing deficits have been reported in unisensory paradigms, it is unknown whether SZ patients (SZP) show altered crossmodal PE processing. We measured high-density electroencephalography a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 69 publications
1
17
0
Order By: Relevance
“…However, this was not the case. Recently, Stekelenburg et al (2013) and Roa Romero et al (2016b) also reported group differences in multisensory ERPs without showing effects in behavioral data. In an interesting framework on multisensory processing, Bizley et al (2016) suggested different stages of multisensory integration, in which the initial integrative processing can occur, at least partially, independent of later perception-related processing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this was not the case. Recently, Stekelenburg et al (2013) and Roa Romero et al (2016b) also reported group differences in multisensory ERPs without showing effects in behavioral data. In an interesting framework on multisensory processing, Bizley et al (2016) suggested different stages of multisensory integration, in which the initial integrative processing can occur, at least partially, independent of later perception-related processing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to findings of unisensory processing deficits, there is also some evidence for aberrant multisensory processing in SCZ (Foucher et al, 2007; Stekelenburg et al, 2013; Roa Romero et al, 2016a,b; Stevenson et al, 2016; for a review see Tseng et al, 2015). One study examined simultaneity judgments in unisensory and multisensory stimuli and found that SCZ have a lengthened window of simultaneity for unisensory visual, unisensory auditory, and bisensory audiovisual stimuli (Foucher et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuropsychological studies confirm this hypothesis. For instance, decreases in task-related theta band activity have been regularly reported in schizophrenic patients (Popov et al, 2015;Roa Romero et al, 2016; for a review, Galderisi et al, 2009) who have long been associated with motivational impairment and aberrant effort-based decisionmaking (Culbreth et al, 2018). More interestingly for the purpose of this section, theta activity is observed throughout the entire duration of a vigilance task in humans (Boksem et al, 2005;Wascher et al, 2014).…”
Section: The Effort Signal As a Product Of The Synchronized And Rhythmentioning
confidence: 91%
“…Similar to the analysis of ERPs, time-frequency power was split according to the conditions and averaged for the electrode pair PO7/PO8. It was then examined for periods of significant interaction of the between-subjects factors Group (OW/OB and NW) and the within-subjects factor Condition (neutral, low-calorie, highcalorie) in the time window from stimulus onset (0 ms) to 1000 ms using a repeated measures ANOVA [59]. To account for alpha error accumulation due to multiple testing, 3dClust-Sim (http://afni.nimh.nih.gov/afni/) [60,61] was used to estimate the probability of false positives.…”
Section: Methodsmentioning
confidence: 99%